Perancangan Tata Letak Gudang Delivery Produk Karpet Kendaraan Roda Empat Menggunakan Pendekatan Systematic Layout Planning di PT Kotobukiya Indo Classic Industries - Ramdani, Dani; Ramdhani, Rizky Fajar (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to redesign the layout of the delivery warehouse for four-wheeled vehicle carpet products at PT Kotobukiya Indo Classic Industries (KICI) using the Systematic Layout Planning (SLP) approach. The main problems identified include the accumulation of goods in the over part area, inefficient material flow, and limited warehouse capacity, which impact delivery delays. The research method was conducted through direct observation, collection of inflow–outflow data of parts, and analysis of activity relationships using relationship diagrams. The results indicate that the existing warehouse capacity is unable to accommodate the production volume of major customers such as (TMMIN), with inflow reaching 4,171 units per month for certain parts. The SLP-based layout redesign resulted in a new warehouse configuration with shorter forklift movement paths, more systematic space arrangement, and more consistent implementation of the FIFO system. The findings conclude that the application of SLP can improve material flow efficiency, reduce handling time, and increase the effective warehouse capacity.